MiR-182 antagonist alleviates glucocorticoid-induced secondary bone degeneration and osteoclast differentiation - Zhao, Bin; Luo, Min; Wang, Aiyuan; Zhang, Weili (Cellular and Molecular Biology, 2022)
In this study, the expression of miR-182 in secondary bone degeneration was investigated, and the effect of its antagonist on glucocorticoid-induced osteoclast differentiation and its mechanism was studied. For this purpose, PBMC cell lines were selected for cultivation, and the changes were observed by hematoxylin-eosin (HE) staining. Real-time fluorescence quantitative (qRT-PCR) was used to detect mRNA expression. The protein expressions of RANKL, OPG and CXCL10 were detected by Western blot. CCK-8 and flow cytometry was used to detect cell proliferation and apoptosis. The results showed that protein expression levels of RANKL, OPG and CXCL10 in the miR-182 group were significantly higher than those in other groups (P>0.01). The miR-182 can promote RANK signal transduction in osteoclasts by regulating RANKL/NFκB signaling pathway, accelerating osteoclast proliferation and differentiation, and slowing down the process by miR-182 inhibitor. In general, miR-182 alleviates OP by inhibiting the activity of osteoclast via RANKL/NFκB signaling.